Universal cements: dual activated and chemically activated - Eliane de Lima; Ricardo Santos; Márcia Durão; Armiliana Nascimento; Rodivan Braz (Taylor & Francis Group, 2016)
Objective: The aim of the present study was to assess the bond strength of universal cements cured either dually or chemically only. Methods: Three cements were assessed using different types of application: dual activated (DA) or chemically activated (CA). In total 80 dentin blocks were used, obtained through the enamel wear of the lingual and buccal surfaces of bovine incisors. Standard cone-shaped cavity preparations were created using diamond burs. Subsequently, indirect restoration blocks were designed with Filtek Z350 (3M ESPE) composite resin. The teeth were divided into two groups (DA and CA) and then subdivided into four subgroups (n = 10) prior to cementation with the respective products: Duo-Link (Bisco); RelyX Ultimate (3M ESPE); Nexus 3 (Kerr) and conventional RelyX ARC (3M ESPE) as the control. The cementation in the PA group was applied following the manufacturer's instructions. The CA group was cemented in a darkroom to avoid exposure to light. They were stored in distilled water at 37 °C for 24 h and submitted to the push-out test. Data were analyzed by two-way ANOVA and Tukey's post-hoc test (p < .05). Results: The greatest bond strength results were obtained for photoactivated universal cements. Conclusion: Chemical activation is not sufficient to ensure acceptable bond strength.